56-23(67+x)=23-13x

Simple and best practice solution for 56-23(67+x)=23-13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56-23(67+x)=23-13x equation:


56-23(67+x)=23-13x

We simplify the equation to the form, which is simple to understand
56-23(67+x)=23-13x

Reorder the terms in parentheses
56+(-1541-23x)=23-13x

Remove unnecessary parentheses
+56-1541-23x=+23-13x

We move all terms containing x to the left and all other terms to the right.
-23x+13x=+23-56+1541

We simplify left and right side of the equation.
-10x=+1508

We divide both sides of the equation by -10 to get x.
x=-150.8

See similar equations:

| n+5=-20 | | x+5x+2=16 | | .12t-.6=.06 | | (5(67)-x)-35+14=13-11 | | x+5x+2=58 | | 2(3-4z)-4(2z+1)=5z-2 | | x+xy+y=11 | | 3x-71=91-6x | | 2x+1=151 | | y-.6y=204 | | 24+8x=-12x-51 | | 3r-7=13+2r | | 2n-18=-15+n | | 5x+9x=56 | | -3w-4.6=5.9 | | 5x-9x=56 | | 0.75f+5=-5 | | 24+8x=12x-51 | | v+v-31.6+v+24.7=189.9 | | -10x-24=-224 | | 9x-13=41 | | 2x+9=3x+2 | | w/6+0.625=-1.375 | | -4x-42=14-6x | | 2x-3+5=3x*4 | | 7z+4.2=2.8 | | 9x+71-7x-18=3x+5 | | 3.7r=9 | | -0.28571428571m=-6 | | 4x+140=9x-5 | | a+a-2=a+4-a+2 | | v+(v-30.4)+(v+26.7)=195.5 |

Equations solver categories